The Necessity and Importance of Religious Harmony In Establishing Peace, A Research and Analytical Study In the Light of Quran and Sunnah - Dr. Hafiz Muhammad Arshad Iqbal,; Dr. Aftab Ahmad,; Ms. Maryam Qasim,; Dr. Muhammad Inamullah, (Al-Qanṭara, 2023)
Peace is very important for the development of society. So, it has been an important issue since time immemorial and it has become more important in today's magical age. All the prophets who came to this world from Hz. Adam (A.S.) to Hz. Muhammad (PBUH) have given importance to the restoration of peace and order, the end of injustice and oppression and the fulfillment of rights. When Hz. Ibrahim (A.S.) and his son Ismail (A.S.) were engaged in the construction of the Kaaba, they prayed for the city of Makkah: “O my Lord, make this city (Makkah) a place of peace”. Today, just as a person is worried due to other problems, in the same way, due to the bad situation of law and order in the society, there is no peace in their life, although the best person is the one whose language and speech not only the other person should be protected, but he should establish a relationship of love with them, being a human being every person wants to live a peaceful life, but despite this, the market of extremism and corruption is hot in the society. The requirement of love of the Messenger of Allah ﷺ is to establish a society where human beings not only respect and honor other human beings but also take care of animals and plants. In the same way, paying the rights of people belonging to non-Muslim sects is necessary to establish peace in the society. There should be religious harmony in the country. Therefore, in this paper, the importance and need of religious harmony in the light of Quran and Sunnah has been highlighted regarding the establishment of peace. Keywords; Necessity of Peace, Religious Harmony, Analytical Study, Quran, and Sunnah